Caso clínico de un adulto con trastorno de personalidad obsesivo-compulsiva según clasificación del DSM-V (2021)
This research presents the clinical case of an adult suffering from obsessive-compulsive personality disorder. The purpose is to present in detail the procedure followed in the psychology clinics of the University of Ibague by integrating cognitive and humanistic techniques to demonstrate the effectiveness and viability of this treatment and its application. The results obtained show relevant improvements such as: greater cognitive flexibility, decrease in physiological activation due to emotional disturbance and anxiety in the face of lack of control, acquisition of problem-solving skills, emotional self-control and thoughts about the perception of oneself and others. It is concluded that the intervention was satisfactory.